2011
DOI: 10.1099/mic.0.045005-0
|View full text |Cite
|
Sign up to set email alerts
|

Dur3 is the major urea transporter in Candida albicans and is co-regulated with the urea amidolyase Dur1,2

Abstract: Hemiascomycetes, including the pathogen Candida albicans, acquire nitrogen from urea using the urea amidolyase Dur1,2, whereas all other higher fungi use primarily the nickel-containing urease. Urea metabolism via Dur1,2 is important for resistance to innate host immunity in C. albicans infections. To further characterize urea metabolism in C. albicans we examined the function of seven putative urea transporters. Gene disruption established that Dur3, encoded by orf 19.781, is the predominant transporter. [14C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 36 publications
3
36
1
Order By: Relevance
“…Therefore, it is expected that these permeases have a role in virulence. Interestingly, the Dur3 deletion mutant was not attenuated in systemic virulence (45). However, our results found that although deletion of DUR3 reduced spermidine uptake by half, deletion of both DUR3 and DUR31 was required for the most extensive reduction in spermidine transport.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…Therefore, it is expected that these permeases have a role in virulence. Interestingly, the Dur3 deletion mutant was not attenuated in systemic virulence (45). However, our results found that although deletion of DUR3 reduced spermidine uptake by half, deletion of both DUR3 and DUR31 was required for the most extensive reduction in spermidine transport.…”
Section: Discussioncontrasting
confidence: 46%
“…Bensen et al (43) first referred to C. albicans orf19.6656 as DUR3, and it became the standard name. Later Braun et al (44) and Navarathna et al (45) referred to C. albicans orf19.781 (as well as orf19.6656) as DUR3. Our homology analyses illustrate the pitfalls in the existing nomenclature.…”
Section: Identification Of C Albicans Dur Transporter Family Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The top five induced transporters were two putative urea permeases dur3-1 (UMAG_02625) and dur3-2 (UMAG_06253), two putative oligopeptide transporters (OPT) opt2 (UMAG_11057) and opt4 (UMAG_02387), and the candidate methylammonium permease (MEP) ump2 (UMAG_05889) (Supplemental Data Set 11, Figures 4A and 4D). In fungi, related transporter families are required for nitrogen utilization from peptides, urea and ammonium, respectively (ElBerry et al, 1993;Lorenz and Heitman, 1998;Hauser et al, 2001;Abreu et al, 2010;Hartmann et al, 2011;Navarathna et al, 2011;Dunkel et al, 2013), while OPTs can also mediate sulfur utilization by taking up glutathione (Bourbouloux et al, 2000). All five transporters are located in the magenta expression module ( Figure 2C), and are thus linked to biotrophy (Supplemental Data Set 11).…”
Section: Nitrogen Transportersmentioning
confidence: 99%
“…In addition to transporting urea into yeast cells, it also facilitates the uptake of polyamines and regulates intracellular boron concentrations (16,17). However, the existence of preponderant nitrogen, such as polyamines, would repress the expression of urea permease (6,17,18).…”
Section: Transport Of Urea Into Engineered Yeast Cells By the Overexpmentioning
confidence: 99%